ARCHETYPAL ETHOS: “TRIPTIC (TRIPTYCH)” BY ADRIAN POP - BANCIU, Ecaterina (Studia Universitatis Babes-Bolyai Musica, 2016)
Important personality of the musical life in Cluj, composer and professor Adrian Pop (*1951) is the last of Sigismund Toduţă’s disciples, the great mentor of the Cluj School of composition. He continued his studies under the guidance of Cornel Ţăranu, one of the most representative composers of the Romanian Avant-garde, together with Hans-Peter Türk, Ede Terényi, Vasile Herman and others, who were themselves Toduţă’s students. Adrian Pop’s style reflects his preference for the national ethos, specific to the Eastern European composition Schools, protruded by the composition techniques of Western Avant-garde. The complex musical language is the result of long years of study in Romania, with personalities such as Ștefan Niculescu and Aurel Stroe, as well as in European musical centres, with Dieter Salbert (Bayreuth), Ton de Leeuw (Burgas), Joji Yuasa (Amsterdam). The impact of his works on audiences has materialized in national awards from the Composers’ Union (1978, 1980, 1989), the Romanian Academic Society Award (1996) as well as international ones, in Tours (1978), Arezzo (1979), Trento (1982, 1984, 1986), Roodeport – South Africa (1983), Spittal an der Drau (1986). His compositions impress both by their variety and themes, of folkloric inspiration, and by their refined polyphonic or heterophonic writing, as learned from his father, Dorin Pop, an excellent choir conductor and specialist in Renaissance music. Actually, his first successful work, Colinda de pricină (Reason Carol), inspired by the folklore in the Sălaj county and introduced to the audiences by Dorin Pop, conductor of the Cappella Transylvanica choir, was loved by the public even from its first performance and remained in the repertoire of all prestigious choirs ever since. This carol also leaves a mark on his future creations of folkloric inspiration. One of the distinctive aspects of his compositional style is the use of folklore in the form of a quoted song later metamorphosed in an ingenious counterpoint weaving. The subject of the present study is the most recent symphonic opus of composer Adrian Pop, the ballet Triptic (Triptych) (1998, rev. 2013). The work continues the series of symphonic creations, Etos I (1976) – on the theme from Mioriţa, a ballad from Sălaj county and Solstiţiu (Solstice) (1979) – a carol of the Sun “which was sung until recently in Bihor county”, as Adrian Pop says. Triptych reunites three different worlds of the 19th century Transylvania, in the three contrasting movements of the “little suite”: the first part evoques a savage world of fantastic realism, with tragic ending, an aspect which preoccupied the composer at the time, as it is also the subject of his doctoral thesis, Recviemul Românesc (Romanian Requiem) (2001). The second part, an idyllic progress of a couple’s life, is the passage to the whirling twirl of a folk song from Ţara Moţilor (the third part). The melodramatic melody treated heterophonically in the picturesque rhythms of Ardeal folklore and spiced up with specific timbres of the semantron and bells, lead the Triptych and its author, composer Adrian Pop, towards success in concert halls and give the audiences the hope for a new choreographic staging.